Ambulatory and Hospital-based Quality Improvement Methods in Israel - Nava Blum; Dafna Halperin; Youssef Masharawi (SAGE Publishing, 2014)
This review article compares ambulatory and hospital-based quality improvement methods in Israel. Data were collected from: reports of the National Program for Quality Indicators in community, the National Program for Quality Indicators in Hospitals, and from the Organization for Economic Cooperation and Development (OECD) Reviews of Health Care Quality.